Antibodies against Rickettsiaceae in dogs of Setúbal, Portugal - Bacellar, F; Dawson, J E; Silveira, C A; Filipe, A R (Central European journal of public health, 1995)
An indirect fluorescent antibody test was performed on sera collected from dogs housed in the municipal kennel of Setúbal to assess the prevalence of antibodies to Ehrlichia canis, the causative agent of canine ehrlichiosis and to Rickettsia conorii, agent of boutonneuse fever in humans. Two other members of the family Rickettsiaceae, Coxiella burnetii and Rickettsia typhi, were included in the serosurvey. Of the 104 dogs tested, 85.6% had antibodies to R. conorii, 50% to E. canis, 26.9% to R. typhi, and 4.8% to C. burnetii. These high seroprevalence rates of dogs with antibodies all year around against Rickettsiaceae suggest that physicians, public health officers and veterinarians should more frequently consider the diagnosis of these infections in Portugal.
Keywords: protilátky bakteriální; Prevalence; surveillance populace; Dogs; zvířata; psi; Fluorescent Antibody Technique; Coxiella; roční období; Portugal; Rickettsia Infections; Dog Diseases; Ehrlichia; mužské pohlaví; nemoci psů; Disease Reservoirs; zdroje nemoci; Portugalsko; Seasons; Population Surveillance; Rickettsia; ženské pohlaví; rickettsiové infekce; Animals; Antibodies, Bacterial; prevalence; fluorescenční protilátková technika; Male; Female